2000
DOI: 10.1253/jcj.64.385
|View full text |Cite
|
Sign up to set email alerts
|

Primary Pericardial Mesothelioma Presenting As Constrictive Pericarditis

Abstract: Primary malignant pericardial mesothelioma is a rare tumor and the case reported here presented as constrictive pericarditis. The patient's symptoms progressed day by day despite treatment with digitalis, diuretics and catecholamines. Although a computed tomographic scan of the chest, echocardiography and pericardiocentesis were performed, a preoperative definitive diagnosis could not be obtained. Emergency pericardiectomy and partial resection of the tumor were carried out with the aid of a percutaneous cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…After this no extent review has been made. Our review includes 29 cases in English literature from 1993 through 2008 where the diagnosis of primary pericardial mesothelioma was established [5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29]. It also includes the findings from our patient and the review, presented in table 1 and table 2.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…After this no extent review has been made. Our review includes 29 cases in English literature from 1993 through 2008 where the diagnosis of primary pericardial mesothelioma was established [5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29]. It also includes the findings from our patient and the review, presented in table 1 and table 2.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…Malignant tumor of the heart (malignant lymphoma, angiosarcoma, mesothelioma, breast cancer or lung cancer), irrespective of the primary or metastatic tumor, is commonly invasive to the pericardium or myocardium, which often results in diastolic dysfunction and some of these cases present with CP. 9,10 Radical pericardiectomy is the definitive treatment for constriction and it is emphasized that timely surgery is needed. 11,12 However, the perioperative mortality is relatively high, especially in cases showing severe impairment of visceral pericardium, severe liver dysfunction, intense calcification of the pericardium and complicated myocardial damage.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown the efficacy of surgery, radiotherapy, and chemotherapy, but the results are modest and provide no significant difference in prognosis, which remains poor (the median survival is about six months from diagnosis) (5,16). The most frequent causes of death are cardiac tamponade, vena cava occlusion, and congestive heart failure (11,12,17).…”
Section: Discussionmentioning
confidence: 99%
“…The factors contributing to the low incidence of its antemortem diagnosis include the paucity and non-specific nature of the clinical signs and symptoms. Diagnosis is most often made by cytological and histopathological examination (8)(9)(10)(11)(12)(13)(14). Even then, the diagnosis may not be readily apparent on morphology alone and one may need to resort to immunohistochemistry and ultrastructural examination.…”
mentioning
confidence: 99%